A Breath of Fresh Air on the Mesenchyme: Impact of Impaired Mesenchymal Development on the Pathogenesis of Bronchopulmonary Dysplasia - Chao, Cho-Ming; El Agha, Elie; Tiozzo, Caterina; Minoo, Parviz; Bellusci, Saverio (Frontiers in Medicine, 2015)
The early mouse embryonic lung, with its robust and apparently reproducible branching pattern, has always fascinated developmental biologists. They have extensively used this embryonic organ to decipher the role of mammalian orthologues of Drosophila genes in controlling the process of branching morphogenesis. During the early pseudoglandular stage, the embryonic lung is formed mostly of tubes that keep on branching. As the branching takes place, progenitor cells located in niches are also amplified and progressively differentiate along the proximo-distal and dorso-ventral axes of the lung. Such elaborate processes require coordinated interactions between signaling molecules arising from and acting on four functional domains: the epithelium, the endothelium, the mesenchyme and the mesothelium. These interactions, quite well characterized in a relatively simple lung tubular structure remain elusive in the successive developmental and postnatal phases of lung development. In particular, a better understanding of the process underlying the formation of secondary septa, key structural units characteristic of the alveologenesis phase, is still missing. This structure is critical for the formation of a mature lung as it allows the subdivision of saccules in the early neonatal lung into alveoli, thereby considerably expanding the respiratory surface. Interruption of alveologenesis in preterm neonates underlies the pathogenesis of chronic neonatal lung disease known as Bronchopulmonary Dysplasia or BPD. De novo formation of secondary septae appears also to be the limiting factor for lung regeneration in human patients with emphysema. In this review, we will therefore focus on what is known in terms of interactions between the different lung compartments and discuss the current understanding of mesenchymal cell lineage formation in the lung, focusing on secondary septa formation.